Reinventing the artistic self: Coetzee's summertime and Matar's In the country of men - ElBowety, Rana Mounir (AUC Knowledge Fountain, 2015)
This thesis attempts to explore the revival of the Kunstlerroman genre in two contemporary works of autobiographical fiction: J. M. Coetzee's Summertime (2009) and Hisham Matar's In the Country of Men (2006). The two main goals are to examine how an artist (author) reveals elements that have shaped his childhood in their writing in an attempt to reinvent the self in an artistic framework, and to understand how different genres transgress their boundaries to form hybrid genres that do not conform to the norms and conventions of one specific genre. I also explore the intertwining figures of the author, narrator, and protagonist of a story in an attempt to understand the aesthetics of the relationship between the author of a text and the hero he creates. To explain the term 'autobiography' and what it denotes, I refer to several major autobiography theorists such as Philippe Lejeune, Paul John Eakin, and James Olney. Additionally, I resort to an essay by Mikhail Bakhtin to decipher the dynamics of the relationship between the author and the hero. The reinvention of the self is a process requiring reliance on recalling the past through memory, which means all that is remembered is somewhat fictionalized and re-ordered; absolute truth cannot be represented. Coetzee and Matar do not only reinvent the self in writing; they consciously and actively participate in the creation of texts that transcend genres, hence defy definition according to set conventions. The outcome is narratives that reveal the reconstruction of the past in writing and new forms that constantly evolve and never fully belong to one particular genre. While Summertime resists constituting a definitive subject/protagonist, In the Country of Men goes beyond individual life to cover 'everyman'.